2015
DOI: 10.5603/piap.2015.0026
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Safety of Two Bronchodilators’ Fixed-Dose Combination: Indacaterol and Glycopyrronium

Abstract: Combination therapy with anticholinergics and β2-agonists should be used in COPD patients after failure of previous monotherapy with one of these drugs. Synergistic effect of both mechanisms of bronchodilation can maximize the efficacy of separately administered drugs. The effectiveness of the combination of LABA and LAMA is already confirmed, nevertheless the question about the safety profile of this therapy is still remaining, particularly with regard to the cardiovascular system. The paper discusses the ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…This is in line with previous studies investigating other LAMA/LABA combinations, which also concluded that the rate of cardiovascular adverse events was comparable with both placebo and monotherapies. 31,32 Furthermore, studies assessing combined LABA/ICS treatment have shown it to be well tolerated, with no adverse effects on mortality or cardiovascular outcomes. 33,34 Some studies, such as the CLAIM study 21 and a further study by Stone et al, 22 have also suggested that bronchodilation can have a positive effect on heart function by reducing hyperinflation.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with previous studies investigating other LAMA/LABA combinations, which also concluded that the rate of cardiovascular adverse events was comparable with both placebo and monotherapies. 31,32 Furthermore, studies assessing combined LABA/ICS treatment have shown it to be well tolerated, with no adverse effects on mortality or cardiovascular outcomes. 33,34 Some studies, such as the CLAIM study 21 and a further study by Stone et al, 22 have also suggested that bronchodilation can have a positive effect on heart function by reducing hyperinflation.…”
Section: Discussionmentioning
confidence: 99%